2020
DOI: 10.1002/adfm.201908371
|View full text |Cite
|
Sign up to set email alerts
|

From Molecular Precursors to Nanoparticles—Tailoring the Adsorption Properties of Porous Carbon Materials by Controlled Chemical Functionalization

Abstract: Nanoporous carbon materials (NCMs) provide the "function" of high specific surface area and thus have large interface area for interactions with surrounding species, which is of particular importance in applications related to adsorption processes. The strength and mechanism of adsorption depend on the pore architecture of the NCMs. In addition, chemical functionalization can be used to induce changes of electron density and/or electron density distribution in the pore walls, thus further modifying the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 223 publications
(160 reference statements)
0
39
0
Order By: Relevance
“…[ 3 ] X‐ray photoelectron spectroscopy (XPS) is a surface analysis technique that provides chemical and electronic state information, making it suitable for characterizing and understanding the local bonding environment of chemical species. [ 107 ] And thermogravimetric analysis (TGA) is carried out to provide first‐hand information to investigate the thermal stability of C 2 N. The C 2 N materials are really noble, and they are hard to oxidize and combust. The oxidation stability could be display in TGA test under air conditions.…”
Section: Characterization Of C2nmentioning
confidence: 99%
“…[ 3 ] X‐ray photoelectron spectroscopy (XPS) is a surface analysis technique that provides chemical and electronic state information, making it suitable for characterizing and understanding the local bonding environment of chemical species. [ 107 ] And thermogravimetric analysis (TGA) is carried out to provide first‐hand information to investigate the thermal stability of C 2 N. The C 2 N materials are really noble, and they are hard to oxidize and combust. The oxidation stability could be display in TGA test under air conditions.…”
Section: Characterization Of C2nmentioning
confidence: 99%
“…Currently, substantial progresses have been made in the methodology to tune the texture structures of carbon-based supports to improve the performance of supported metal catalysts. [228][229][230][231][232][233][234] The extension of Stöber method for the preparation of carbon-based supports opens up new areas of carbon spheres. 235,236 Carbon-based supports impregnated with highly monodispersed metal nanoparticles have been successfully made and applied in catalysis.…”
Section: New Trends and Prospectsmentioning
confidence: 99%
“…With an increase in the number of comprehensive studies, the self-doping strategy has been recently subdivided into adding a supplementary dopant (e.g., ethanediamine or phosphoric/boric acid) to the carbon precursors before pyrolyzing or the direct pyrolysis of organic salt/polymer precursors assembled by heteroatomcontaining building blocks. 123 The supplementary dopant can not only provide plentiful heteroatoms, but also serve as a catalyst, stabilizer, activator, or structure-directing agent. For example, Jia's group synthesized chitosan-derived N/B-codoped porous carbon nanosheets with three amino acids and boric acid as the N/B source.…”
Section: Heteroatom Functionalizationmentioning
confidence: 99%
“…Wang's group demonstrated that the presence of poly(ionic liquid)s was beneficial for optimizing the hydrothermal carbonization of sugar precursors for N-doped porous carbon nanoparticles, wherein the poly(ionic liquid) chains introduced electrostatic repulsion for minimized particle agglomeration and unexpectedly functioned as the pore former and N supply. 125 As an extension of the post-doping strategy, the one-step doping activation is frequently applied via directly calcining the mixtures of carbon precursors and heteroatomdoped activators, 123 and the resultant N-rich microporous carbons activated by NaNH 2 afforded outstanding capacitance of 350.2 F g À1 at 1 A g À1 in 6 M KOH with excellent rate retention of 74.2% at 10 A g À1 . 126 Another desirable route toward fabricating functionalized carbons at a higher doping level is the direct pyrolysis of organic salt/polymer precursors (e.g., metal complexes, conjugated polymer networks, ionic liquids, and poly(ionic liquid)s).…”
Section: Heteroatom Functionalizationmentioning
confidence: 99%